2019
DOI: 10.1016/j.brs.2018.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Individual white matter bundle trajectories are associated with deep brain stimulation response in obsessive-compulsive disorder

Abstract: Background: The ventral anterior limb of the internal capsule (vALIC) is a target for deep brain stimulation (DBS) in obsessive-compulsive disorder (OCD). Conventional surgical planning is based on anatomical landmarks. Objective/hypothesis: We hypothesized that treatment response depends on the location of the active DBS contacts with respect to individual white matter bundle trajectories. This study thus aimed to elucidate whether vALIC DBS can benefit from bundle-specific targeting. Methods: We performed tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 30 publications
3
72
0
Order By: Relevance
“…This potentially misleading nomenclature of the surgical sl-MFB target has suggested that results in two previous OCD studies would be conflicting, while anatomically, their results agreed. Both studies favored a similarly defined tract within the ALIC, which was referred to as sl-MFB in one study 65 and as anterior thalamic radiation in the second 30 . To readers, this suggested conflicting results while they were actually confirmatory (based on the location of both tracts within the ALIC).…”
Section: Discussionmentioning
confidence: 99%
“…This potentially misleading nomenclature of the surgical sl-MFB target has suggested that results in two previous OCD studies would be conflicting, while anatomically, their results agreed. Both studies favored a similarly defined tract within the ALIC, which was referred to as sl-MFB in one study 65 and as anterior thalamic radiation in the second 30 . To readers, this suggested conflicting results while they were actually confirmatory (based on the location of both tracts within the ALIC).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the work on sIMFB stimulation and our previous finding that proximity of stimulation to sIMFB was related to treatment response in OCD ( Liebrand et al, 2019 ), we hypothesize that stimulation more proximal to the slMFB within the ALIC is also beneficial for treatment response in TRD. However, a possible role of the ATR and thalamus cannot be ruled out, given reported structural changes within the thalamus ( Kempton, 2011 ), and hyperactivity of the pulvinar nucleus in MDD patients ( Hamilton et al, 2012 ).…”
Section: Introductionmentioning
confidence: 90%
“…Three recent studies have suggested that the VTApp within ALIC (which may represents the hyperdirect cortical-STN connection), may be a critical fiber tract leading to clinical response in DBS for OCD (Baldermann et al, 2019;Liebrand et al, 2019;Li et al, 2020). ALIC fibers associated with a good outcome have been postulated to run dorsal to the NAc, near the bed nucleus of the stria terminalis, entering the ventral part of the thalamus at the border of the anterior and inferior thalamic peduncle (Baldermann et al, 2019).…”
Section: Ventral Striatum/ventral Capsulementioning
confidence: 99%